Relative head injury risk sustained from basic judo throw techniques learning in 1st and 2nd years of junior high school - Koshida, S.; Ishii, T.; Matsuda, T.; Hashimoto, T. (Association for the Scientific Studies on Judo, Kodokan, 2019)
Previous studies have reported that head injuries sustained during judo frequently occur when an opponent throws a novice judo practitioner, suggesting that identifying the relative head injury risk of the breakfall for judo throws may be important when teaching judo to young students in a school setting. Therefore, the objective of this study was to investigate the biomechanical parameters that represent head injury risk during the breakfall motion of various judo-throw techniques in novice judo practitioners. Seven male novice judo practitioners volunteered to attend the study (median age: 20 years, height: 1.69 m, weight: 69.4 kg). Forty-one reflective markers were assigned to the anatomical landmarks of the participants to define individual body segments. The kinematic data during the breakfallmotion for five judo-throw techniques (sasae-tsurikomi-ashi, hiza-guruma, ogoshi, tai-otoshi, and osoto-gari) was collected using a three-dimensional motion analysis method (500 Hz). We obtained the time course of the head resultant acceleration and head resultant rotational velocity through the breakfall motion and computed peak values of each biomechanical parameter. The Wilcoxon test with the Holm correction was performed to test the difference in each biomechanical parameter between the breakfalls for the different throws. The present study demonstrated that there was no significant difference between the peak values of the breakfalls for the different judo throws, suggesting that stress imposed to the head segment during breakfalls was not different among the throws. Previous epidemiological studies have indicated that being thrown with osoto-gari gives the greatest risk for sustaining a judo-related head injury in novice judokas. However, our results suggest that this throw may not carry the greatest risk of judo-related head injury among the basic judo throws. In addition, it is noteworthy that the peak values of neither the resultant acceleration or resultant angular acceleration during the breakfall exceeded the head injury tolerance levels that have been reported in the previous studies.